PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN MEDIA DIORAMA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V DI SD NEGERI MEUNASAH TUTONG ACEH BESAR - Wulannurhasan; Rahmi, Putri (Jurusan Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2024)
This study aims to improve student learning outcomes, describing class V SD Negeri Meunasah Tutong Aceh Besar. The type of research used is classroom action research consisting of 2 cycles. Each cycle includes the stages of planning, implementation, observation and reflection. The subject of this research is the fifth grade students of SD Negeri Meunasah Tutong Aceh Besar consisting of 16 students with details of 8 students and 8 female students. The instrument used to describe teacher and student activities in the form of observation sheets, while to reveal data on student learning outcomes using test sheets. The results showed that teacher activity data in cycle I reached 83% while cycle II reached 98% which had increased by 15%. Student activity data in cycle I reached 78% while cycle II reached 94% which had increased by 16%. Data on student learning outcomes in cycle I amounted to 62.5% while in cycle II it reached 87.5% which had increased by 25%. These data show that the application of the think pair share learning model assisted by diorama media can improve teacher activity, student activity and learning outcomes of fifth grade students of SD Negeri Meunasah Tutong Aceh Besar.